2021
DOI: 10.3389/fmicb.2020.611792
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Moss-Associated Cyanobacteria Using Phycocyanin Pigment Extraction

Abstract: In the boreal forest, cyanobacteria can establish associations with feather moss and realize the biological nitrogen fixation (BNF) reaction, consisting in the reduction of atmospheric dinitrogen into bioavailable ammonium. In this ecosystem, moss-associated cyanobacteria are the main contributors to BNF by contributing up to 50% of new N input. Current environmental changes driven by anthropogenic activities will likely affect cyanobacteria activity (i.e., BNF) and populations inhabiting mosses, leading to po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 84 publications
(111 reference statements)
1
8
0
Order By: Relevance
“…In our study, we reported a significant positive exponential relationship between moss‐associated N 2 ‐fixation and cyanobacterial biomass (Figure 3). Several studies demonstrated a positive linear relationship between N 2 ‐fixation and the quantity of cyanobacteria on moss in Sweden (DeLuca et al, 2007; Rousk, DeLuca, & Rousk, 2013), Chile (Arróniz‐Crespo et al, 2014) and Canada (Renaudin et al, 2021; Rousk, Degboe, et al, 2017), confirming that N 2 ‐fixation and cyanobacterial biomass are linked. It has been hypothesized that this relationship is the result of the moss controlling the number of colonizing cyanobacteria as a function of its N demand (Bay et al, 2013; Leppänen et al, 2013).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…In our study, we reported a significant positive exponential relationship between moss‐associated N 2 ‐fixation and cyanobacterial biomass (Figure 3). Several studies demonstrated a positive linear relationship between N 2 ‐fixation and the quantity of cyanobacteria on moss in Sweden (DeLuca et al, 2007; Rousk, DeLuca, & Rousk, 2013), Chile (Arróniz‐Crespo et al, 2014) and Canada (Renaudin et al, 2021; Rousk, Degboe, et al, 2017), confirming that N 2 ‐fixation and cyanobacterial biomass are linked. It has been hypothesized that this relationship is the result of the moss controlling the number of colonizing cyanobacteria as a function of its N demand (Bay et al, 2013; Leppänen et al, 2013).…”
Section: Discussionmentioning
confidence: 85%
“…A positive linear relationship between the number of cyanobacteria living on moss and N 2 -fixation activity was reported for various moss species at numerous locations (Arróniz-Crespo et al, 2014;DeLuca et al, 2007;Renaudin et al, 2021;Rousk, Degboe, et al, 2017;, suggesting that higher N 2 -fixation is correlated with higher cyanobacterial biomass on moss. While significant, this relationship only partially explained variability (9%-50%) in N 2 -fixation and is not always observed (Goth et al, 2019).…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…The leaf size and number of cyanobacterial cells for 1755 leaves (90 for A. turgidum , 360 for P. schreberi , 360 for T. nitens and 945 for H. splendens ) were measured. Microscopic counting, rather than using proxies of cyanobacterial quantity ( Renaudin et al ., 2021 ), enabled us to link leaf traits with cyanobacterial colonization.…”
Section: Methodsmentioning
confidence: 99%